ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI BERDASARKAN METODE FULL COSTING DALAM MENENTUKAN HARGA JUAL (STUDI KASUS UMKM BOLU HARUM WANGI) - Cita Rizki; Sihabudin Sihabudin; Robby Fauji (Journal of Economic, Bussines and Accounting (COSTING), 2024)
UMKM Harum Wangi cake is a business operating in the culinary sector which produces various cakes such as sponge cake, brownies and donuts. One of the obstacles to production is that determining the selling price is often inaccurate and causes the determination of the cost of production and raw material costs to be irrelevant, thus giving rise to overhead costs for labor and the production process. This research aims to analyze the calculation of the cost of production based on the full coasting method for UMKM Harum Wangi cake. The method used in this research is quantitative. Based on the research results, it can be seen that perhit. The basic production costs applied by UMKM for Harum Wangi cakes do not yet refer to the full costing method that has been calculated. The difference in cost of production between companies using the Full Costing method is caused by differences in cost allocation which shows that there is an advantage in calculating the cost of production based on the Full Costing method and to be able to determine the cost of goods sold, namely production costs must be calculated at the beginning of each month based on the previous period's sales report. This research aims to calculate the cost of goods for UMKM fragrant cakes using the Full Costing method. Keyword : Price, Production, Fullcosting